Accuracy of experimental mandibular osteotomy using the image-guided sagittal saw. Issue 6 (June 2016) - Pietruski, P.; Majak, M.; Swiatek-Najwer, E.; Popek, M.; Szram, D.; Zuk, M.; Jaworowski, J.
Abstract: The aim of this study was to perform an objective assessment of the accuracy of mandibular osteotomy simulations performed using an image-guided sagittal saw. A total of 16 image-guided mandibular osteotomies were performed on four prefabricated anatomical models according to the virtual plan. Postoperative computed tomography (CT) image data were fused with the preoperative CT scan allowing an objective comparison of the results of the osteotomy executed with the virtual plan. For each operation, the following parameters were analyzed and compared independently twice by two observers: resected bone volume, osteotomy trajectory angle, and marginal point positions. The mean target registration error was 0.95 ± 0.19 mm. For all osteotomies performed, the mean difference between the planned and actual bone resection volumes was 8.55 ± 5.51%, the mean angular deviation between planned and actual osteotomy trajectory was 8.08 ± 5.50°, and the mean difference between the preoperative and the postoperative marginal point positions was 2.63 ± 1.27 mm. In conclusion, despite the initial stages of the research, encouraging results were obtained. The current limitations of the navigated saw are discussed, as well as the improvements in technology that should increase its predictability and efficiency, making it a reliable method for improving the surgical outcomes of maxillofacial operations.